Lutetium Lu 177 vipivotide tetraxetan for metastatic castration-resistant prostate cancer. Issue 11 (2nd November 2022) - Shah, Hina; Ravi, Praful; Sonpavde, Guru; Jacene, Heather
ABSTRACT: Introduction: 177 Lu-vipivotide tetraxetan is a radiopharmaceutical that selectively targets prostate-specific membrane antigen (PSMA) and delivers beta-radiations to kill prostate cancer cells. Areas covered: Extensive experience outside the United States as well as randomized phase II and phase III data demonstrate that 177 Lu-vipivotide tetraxetan is a safe, generally well tolerated, and effective therapy for men with mCRPC. 177 Lu-vipivotide tetraxetan was approved by the FDA in March 2022 for the treatment of PSMA-positive metastatic castration-resistant prostate cancer (mCRPC) after androgen receptor pathway inhibition and taxane-based chemotherapy based on the results of the VISION trial. Expert opinion: This review discusses the development and studies leading to the approval of 177 Lu-vipivotide tetraxetan. In all, 177 Lu-vipivotide tetraxetan is an exciting new tool in the arsenal for men with mCRPC after novel androgen pathway inhibitors and at least one taxane chemotherapy. Optimal selection of patients, sequencing of 177 Lu-vipivotide tetraxetan with the other agents available to treat mCRPC, and the use of dosimetry are current areas of interest with great potential and opportunities for further individual patient optimization using the tools of theranostics.